2013
DOI: 10.2478/v10170-011-0045-8
|View full text |Cite
|
Sign up to set email alerts
|

Multiphase Z-source inverter using maximum constant boost control

Abstract: Multiphase Z-source inverter using maximum constant boost control ABDELLAH KOUZOU and HAITHAM ABU-RUB This paper deals with the impedance source (Z-source) multiphase inverter, where the maximum constant boost control method is studied and analyzed in the general case of number of phases. On the other side the impact of the modulation index and the number of phases on the duty cycle shoot-through and on the gain of the output voltage ranges is presented. To validate advantages of the Z-source multiphase invert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…In 2013, A. Kouzou [5] reported the use of PWM in multiphase systems, in which case amaximum boost control (MBC) strategy for multiphase system from 3, 5, 7, 11, 13, 15, 17, 19 and 21 phases under simulation task were employed. In the experimental setup, the researchers fed two parallel loads, a five-phase resistive load and a five-phase induction machine to verify the simulation result.…”
Section: Motivation and Research Goalmentioning
confidence: 99%
See 3 more Smart Citations
“…In 2013, A. Kouzou [5] reported the use of PWM in multiphase systems, in which case amaximum boost control (MBC) strategy for multiphase system from 3, 5, 7, 11, 13, 15, 17, 19 and 21 phases under simulation task were employed. In the experimental setup, the researchers fed two parallel loads, a five-phase resistive load and a five-phase induction machine to verify the simulation result.…”
Section: Motivation and Research Goalmentioning
confidence: 99%
“…In the experimental setup, the researchers fed two parallel loads, a five-phase resistive load and a five-phase induction machine to verify the simulation result. They found that the system could accomplish any desired output multiphase AC voltage whose magnitude is greater than the input DC voltage [5]. The performance parameters of the system was also improved, which include the decrease in the Z-source capacitor voltage and Z-source inductor current ripple [5].…”
Section: Motivation and Research Goalmentioning
confidence: 99%
See 2 more Smart Citations